PUNK: IDEOLOGI KEBEBASAN DALAM NOVEL AKAR KARYA DEWI LESTARI - Isna, Fariha Nurul; Rohman, Muhamad Fatoni (Fon : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Literary works are social reflections that are created from the union between reality and imagination. To obtain a picture of reality in a literary work, an in-depth study of the literary work is needed. The focus of this study is to investigate the periodization of the punk community and the ideology of punk freedom contained in the novel Akar by Dewi Lestari. The study, which was initiated using a qualitative approach, relies on Alan Swingewood's literary sociology paradigm. The main data source of this research is the novel Akar by Dewi Lestari. The data in this study are in the form of narratives, dialogs, or monologues that allegedly record traces of the punk community and represent the ideology of freedom of the punk community. The data is collected through reading and note-taking techniques. The data that has been collected is then analyzed using content analysis techniques. The results showed that the periodization of the punk community depicted in the novel was in 1996-2001 as evidenced by the beginning of concern for socio-political issues. The existence of the punk community is also supported by the ideology of physical and psychological freedom of the characters. Physical freedom is illustrated in the storytelling of characters who tend to be different from the general public such as hairstyles (spike, and baldy), clothing styles and tattoos on the body. Psychic freedom is reflected in the narratives that describe the thinking style of characters such as Bong who chooses not to be bound to any institution and decision-making on each of Bodhi's journeys of self-discovery.